Delayed ACL Reconstruction in Patients ≥40 Years of Age Is Associated With Increased Risk of Medial Meniscal Injury at 1 Year. Issue 3 (March 2019) - Stone, Jonathan A.; Perrone, Gabriel S.; Nezwek, Teron A.; Cui, Qingping; Vlad, Steven C.; Richmond, John C.; Salzler, Matthew J.
Background: Anterior cruciate ligament (ACL) tears in the pediatric and young adult ACL-deficient knee are often associated with meniscal or chondral injury with delayed time to surgery. The incidence of ACL reconstruction performed in patients aged ≥40 years is rising, and it is unclear if delayed surgery in this cohort similarly affects the health of the meniscus and cartilage. Purpose: To evaluate whether delayed reconstruction in a cohort of patients aged ≥40 years is associated with an increased risk of meniscal or chondral injury. Study Design: Cohort study; Level of evidence, 3. Methods: Records of patients aged ≥40 years who underwent primary arthroscopic ACL reconstruction between 2012 and 2016 at an academic hospital were retrospectively reviewed. Patient characteristic data and time to surgery were recorded. Operative reports were analyzed for meniscal and chondral injuries as well as treatment. Patients were grouped according to time to surgery, defined as early (<90 days) or delayed (≥90 days). Logistic regression modeling was used to form associations between elapsed time to surgery and patient characteristics to meniscal and chondral damage. Additionally, risks for meniscal and chondral injury were analyzed at time points of 180 days and 1 year from injury to surgery. Results: A total of 227 patients met the study criteria: 106 patients underwent early surgery, and 121 underwent delayed surgery. The authors identified 127 medial meniscal tears and 106 lateral meniscal tears. Medial, lateral, and patellofemoral compartment chondral injury was reported in 127, 82, and 130 patients, respectively. Delayed surgery (≥90 days) was not associated with increased risk of medial or lateral meniscal tears or any chondral injury at 90 days. Each year of increased age was associated with an increased odds ratio: 1.09 ( P = .001) for medial meniscal tears, 1.06 ( P = .014) for lateral meniscal tears, 1.10 ( P = .001) for medial compartment chondral injuries, and 1.07 ( P = .007) for patellofemoral compartment chondral injuries. Additionally, each unit of increased body mass index was associated with an increased odds ratio: 1.09 ( P = .039) for medial meniscal tears and 1.14 ( P = .003) for medial compartment cartilage injury. Analysis of 180-day and 1-year time points revealed an increased risk (odds ratio, 3.47; 95% CI, 1.55-7.77; P = .002) for medial meniscal injury when surgery was delayed for >1 year. Conclusion: Delayed ACL reconstruction (≥90 days) among patients aged ≥40 years was not associated with an increased risk of meniscal or chondral injury. Increasing age and body mass index were associated with higher risks of meniscal and chondral injuries in this cohort. Delay in surgery for >1 year was associated with increased risk of medial meniscal tear.